Detection and genotyping of enteric foodborne viruses in ready-to-eat leafy vegetables and berries from Córdoba, Argentina. - Di Cola Bucciarelli, Guadalupe (2025)
The global consumption of ready-to-eat (RTE) leafy green vegetables and berries has risen as consumers perceive them as safe and nutritious options. However, these foods have also been identified as sources of enteric viruses that infect the human gastrointestinal system, which are then excreted and can spread through the fecal-oral route. In Argentina, there is limited evidence on the detection of enteric viruses in food, and no legislation currently requires their detection in frozen or fresh produce intended for domestic consumption. This study aimed to identify and characterize five foodborne viruses with high and low health impact (norovirus, hepatitis A virus, hepatitis E virus, rotavirus, and adenovirus) in berries and RTE leafy vegetables marketed in central Argentina. A total of 242 samples (145 berries and 97 leafy greens) were collected from retail sources in Córdoba and processed according to ISO 15216-2, 2019 standard. Viral detection was performed by qPCR or RT-qPCR, followed by viral characterization through specific RT-PCR assays or Sanger sequencing. Results indicate that 4.2 % (6/145) of berry samples, primarily frozen strawberries, tested positive for norovirus or rotavirus, while 10.3 % (10/97) of leafy green samples were positive for norovirus, rotavirus and adenovirus. Genotyping identified the same genotypes as those associated with local gastroenteritis outbreaks, and phylogenetic analysis showed that the strains were closely related. The absence of hepatitis A and E viruses suggests limited transmission of these pathogens through these foods. This study highlights the need to strengthen hygiene and monitoring protocols for RTE products, as viral contamination poses potential health risks to consumers, underscoring a critical area for improving food safety. //Resumen: El consumo global de vegetales de hoja verde y bayas listos para comer (RTE) ha aumentado a medida que los consumidores los perciben como opciones seguras y nutritivas. Sin embargo, estos alimentos también se han identificado como fuentes de virus entéricos que infectan el sistema gastrointestinal humano, que luego se excretan y pueden propagarse por vía fecal-oral. En Argentina, existe evidencia limitada sobre la detección de virus entéricos en alimentos, y actualmente ninguna legislación exige su detección en productos congelados o frescos destinados al consumo doméstico. Este estudio tuvo como objetivo identificar y caracterizar cinco virus transmitidos por alimentos con alto y bajo impacto en la salud (norovirus, virus de la hepatitis A, virus de la hepatitis E, rotavirus y adenovirus) en bayas y vegetales de hoja RTE comercializados en el centro de Argentina. Se recolectaron un total de 242 muestras (145 bayas y 97 verduras de hoja verde) de fuentes minoristas en Córdoba y se procesaron de acuerdo con la norma ISO 15216-2, 2019 . La detección viral se realizó mediante qPCR o RT-qPCR, seguida de la caracterización viral mediante ensayos específicos de RT-PCR o secuenciación de Sanger. Los resultados indican que el 4,2 % (6/145) de las muestras de bayas, principalmente fresas congeladas, dieron positivo para norovirus o rotavirus, mientras que el 10,3 % (10/97) de las muestras de verduras de hoja verde dieron positivo para norovirus, rotavirus y adenovirus. La genotipificación identificó los mismos genotipos que los asociados con brotes locales de gastroenteritis, y el análisis filogenético mostró que las cepas estaban estrechamente relacionadas. La ausencia de virus de la hepatitis A y E sugiere una transmisión limitada de estos patógenos a través de estos alimentos. Este estudio destaca la necesidad de fortalecer los protocolos de higiene y monitoreo para productos RTE, ya que la contaminación viral plantea riesgos potenciales para la salud de los consumidores, lo que subraya un área crítica para mejorar la seguridad alimentaria.